Ubiquitin-Specific Protease 14 Negatively Regulates Toll-Like Receptor 4-Mediated Signaling and Autophagy Induction by Inhibiting Ubiquitination of TAK1-Binding Protein 2 and Beclin 1 - Min, Yoon; Lee, Sena; Kim, Mi-Jeong; Chun, Eunyoung; Lee, Ki-Young (Frontiers in Immunology, 2017)
Ubiquitin-specific protease 14 (USP14), one of three proteasome-associated deubiquitinating enzymes (DUBs), has multifunctional roles in cellular context. Here, we report a novel molecular mechanism and function of USP14 in regulating autophagy induction and NF-B activation induced by Toll-like receptor (TLR) 4. USP14 interacted with TRAF6 and interrupted the association of Beclin 1 with TRAF6, leading to inhibition of TRAF6-mediated ubiquitination of Beclin 1. Reduced expression of USP14 in USP14-knockdown (USP14KD) THP-1 cells enhanced autophagy induction upon TLR4 stimulation as shown by the increased conversion of cytosolic LC3-I to membrane-bound LC3-II. Moreover, USP14KD human breast carcinoma MDA-MB-231 cells and USP14KD human hepatic adenocarcinoma SK-HEP-1 cells showed increased cell migration and invasion, indicating that USP14 is negatively implicated in the cancer progression by the inhibition of autophagy induction. Furthermore, we found that USP14 interacted with TAB2 protein and induced deubiquitination of TAB2, a key factor in the activation of NF-B. Functionally, overexpression of USP14 suppressed TLR4-induced activation of NF-B. In contrast, USP14KD THP-1 cells showed enhanced activation of NF-B, NF-B-dependent gene expression, and production of pro-inflammatory cytokines such as IL-6, IL-1, and TNF-. Taken together, our data demonstrate that USP14 can negatively regulate autophagy induction by inhibiting Beclin 1 ubiquitination, interrupting association between TRAF6 and Beclin 1, and affecting TLR4-induced activation of NF-B through deubiquitination of TAB2 protein.